2014
DOI: 10.1002/chem.201404307
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Supported on CeO2‐SBA‐15 by Microwave Irradiation Possess Metal–Support Interactions and Enhanced Catalytic Activity

Abstract: Metal-support interactions (MSIs) and particle size play important roles in catalytic reactions. For the first time, silver nanoparticles supported on CeO2-SBA-15 supports are reported that possess tunable particle size and MSIs, as prepared by microwave (MW) irradiation, owing to strong charge polarization of CeO2 clusters (i.e., MW absorption). Characterizations, including TEM, X-ray photoelectron spectroscopy, and extended X-ray absorption fine structure, were carried out to disclose the influence of CeO2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 36 publications
(27 reference statements)
1
24
0
Order By: Relevance
“…Possible explanation can be attributed to the hypochromic effect, 28 in which the interaction with metal ions destabilize the donor part of the chromophore, thus inhibiting donor ability of chromophore. 29 However, the aqueous solution Ce(NO3)3 exhibits the single peak at 5723 eV which can be ascribed to the transition of an electron in Ce 3+ from the Ce core 2p3/2 state up to an empty 5d state mixed with the Ce 4f 1 final state. In addition, both of Pd/MIL-101 and Pd/CeMIL-101 shows the similar absorption behavior to those of the samples without Pd nanoparticles loading.…”
Section: Resultsmentioning
confidence: 99%
“…Possible explanation can be attributed to the hypochromic effect, 28 in which the interaction with metal ions destabilize the donor part of the chromophore, thus inhibiting donor ability of chromophore. 29 However, the aqueous solution Ce(NO3)3 exhibits the single peak at 5723 eV which can be ascribed to the transition of an electron in Ce 3+ from the Ce core 2p3/2 state up to an empty 5d state mixed with the Ce 4f 1 final state. In addition, both of Pd/MIL-101 and Pd/CeMIL-101 shows the similar absorption behavior to those of the samples without Pd nanoparticles loading.…”
Section: Resultsmentioning
confidence: 99%
“…Hot energetic electrons generated from plasmonic H x MoO 3– y under visible light can transfer to the contiguous RuPd NPs. [8b], H x MoO 3– y support is thus positively charged and the surface of RuPd NPs are negatively charged, which may facilitate the dissociation of hydrogen molecules and the subsequent PNP reduction on RuPd NPs. [2b], [8c], Additionally, it was also found that the RuAu/H x MoO 3– y and RuPt/H x MoO 3– y hybrids are more active than Au/H x MoO 3– y and Pt/H x MoO 3– y under visible light irradiation (Figure S9a), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Here, chemical reduction of 4‐nitorophenol (4‐NP) into 4‐aminophenol was performed by a tandem reaction in which Ag serves a dual role to catalyze the dehydrogenation of AB and hydrogenation of 4‐NP. Here, AB was employed as a convenient H 2 source instead of conventional NaBH 4 because of the high stability and nontoxic property of AB 16c. 28…”
Section: Resultsmentioning
confidence: 99%